Being an Early-Career CMS Academic in the Context of Insecurity and 'Excellence': The Dialectics of Resistance and Compliance. Issue 9 (September 2017) - Bristow, Alexandra; Robinson, Sarah; Ratle, Olivier
Drawing on a dialectical approach to resistance, we conceptualise the latter as a multifaceted, pervasive and contradictory phenomenon. This enables us to examine the predicament in which early-career Critical Management Studies academics find themselves in the current times of academic insecurity and 'excellence', as gleaned through this group's understandings of themselves as resisters and participants in the complex and contradictory forces constituting their field. We draw on 24 semi-structured interviews to map our participants' accounts of themselves as resisters in terms of different approaches to tensions and contradictions between, on the one hand, the interviewees' Critical Management Studies alignment and, on the other, the ethos of business school neoliberalism. Emerging from this analysis are three contingent and interlinked narratives of resistance and identity – diplomatic, combative and idealistic – each of which encapsulates a particular mode (negotiation, struggle, and laying one's own path) of engaging with the relationship between Critical Management Studies and the business school ethos. The three narratives show how early-career Critical Management Studies academics not only use existing tensions, contradictions, overlaps and alliances between these positions to resist and comply with selected forces within each, but also contribute to the (re-)making of such overlaps, alliances, tensions and contradictions. Through this reworking of what it means to be both Critical Management Studies scholars and business school academics, we argue, early-career Critical Management Studies academics can be seen as active resisters and re-constituters of their complex field.